Atomized biodegradable dust inhibitor and preparation method thereof

By using atomizable biodegradable dust inhibitors in tunnel boring, the problem of poor dust reduction effect in plateau and high-efficiency dust suppression and environmental protection performance are solved.

CN119463807APending Publication Date: 2025-02-18CHINA RAILWAY TUNNEL GROUP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411484748.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

During the tunnel excavation process in the high-altitude areas of the plateau, the existing water spray dust reduction and ventilation dust reduction technology have limited effects. The polymer dust inhibitor has poor atomization effect under high temperature and low humidity conditions, making it difficult to form an effective film, and cannot meet construction needs and Environmental protection requirements.

Method used

Use atomizable biodegradable dust inhibitors, which consist of chemical polymer materials (such as polyvinyl alcohol, polyacrylate or polyethylene glycol) and natural biopolymer materials (such as chitosan or xanthan gum) Composition, through specific mass ratios and auxiliary agent ratios, its atomization effect and biodegradation performance are improved.

Benefits of technology

It achieves the formation of uniform small droplets under high temperature and low humidity conditions, improves spray uniformity and coverage effect, avoids nozzle blockage, improves dust reduction efficiency, and meets environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005098438470000171
    Figure BDA0005098438470000171
  • Figure BDA0005098438470000181
    Figure BDA0005098438470000181
  • Figure BDA0005098438470000191
    Figure BDA0005098438470000191
Patent Text Reader

Abstract

The invention discloses an atomizable biodegradable dust inhibitor, which comprises an effective component and an auxiliary agent, the effective component is a base material, the base material is composed of a chemical polymer material and a natural biopolymer material, and the chemical polymer material is polyvinyl alcohol, polyacrylate or polyethylene glycol; the natural biopolymer material is chitosan or xanthan gum; the mass percentage content of the effective components is 5-20%, the balance is the auxiliary agent, and the sum of the mass percentage content of the effective components and the auxiliary agent is 100%. The atomization effect of the dust inhibitor is achieved, formed liquid drops are small and uniform, dust can be evenly covered, a nozzle is prevented from being blocked, and the dust falling efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of tunnel dust suppression, and particularly relates to an atomizable biodegradable dust suppressant and a preparation method thereof. Background Art

[0002] During tunneling in high-altitude, cold regions, especially during drill-and-blast tunneling, operations such as drilling, blasting, loading, and ventilation discharges severely disturb the rock, releasing large amounts of dust that becomes suspended in the air. This creates a serious dust problem. Dust not only poses a health threat to construction workers but also affects vision and equipment operation, increasing safety risks. The low air pressure and slow air flow in the plateau environment, especially when temperatures inside tunnels can reach 30°C, exacerbate dust dispersion and pose a greater threat.

[0003] Existing technologies, such as water spraying and ventilation, have limited effectiveness in these conditions: water spraying can easily make the tunnel slippery, and ventilation is less effective in low-pressure environments. Existing polymer dust suppressants, due to their large molecular weight, are difficult to dissolve and prepare on-site. Their high viscosity also makes them prone to nozzle clogging during spraying. Furthermore, they exhibit poor atomization under high temperatures and low humidity, making it difficult to form an effective film. These agents, however, do not meet both construction and environmental requirements. Summary of the Invention

[0004] The purpose of the present invention is to provide an atomizable biodegradable dust suppressant and a preparation method thereof. The atomization effect of the dust suppressant forms small and uniform droplets, which can evenly cover the dust, prevent nozzle clogging, and improve dust reduction efficiency.

[0005] The present invention adopts the following technical solution: an atomized biodegradable dust suppressant, comprising an active ingredient and an adjuvant, wherein the active ingredient is a base material, and the base material is composed of a chemical polymer material and a natural biological polymer material, wherein the chemical polymer material is polyvinyl alcohol, polyacrylate or polyethylene glycol; and the natural biological polymer material is chitosan or xanthan gum;

[0006] The mass percentage of the active ingredient is 5-20%, the balance is auxiliary agent, and the sum of the mass percentages of the active ingredient and the auxiliary agent is 100%.

[0007] Furthermore, the mass ratio of the chemical polymer material to the natural biological polymer material is 6.5-7.5:3.

[0008] Furthermore, the auxiliary agent comprises the following ingredients:

[0009] Thickener: 0.5-2%;

[0010] Solvent: 72.2-93.3%;

[0011] Film-forming aid: 1-5%;

[0012] Surfactant: 0.1-0.5%;

[0013] Preservatives: 0.1-0.3%;

[0014] The solvent is a mixture of water and ethanol, wherein the mass content of water is 90-95% and the mass content of ethanol is 5-10%.

[0015] Further, the thickener is hydroxypropyl methylcellulose;

[0016] The film-forming aid is an acrylic acid copolymer;

[0017] The surfactant is sulfosuccinate;

[0018] The preservatives are phenoxyethanol and disodium edetate, and the mass ratio of phenoxyethanol to disodium edetate is 2:1.

[0019] Furthermore, the molecular weight of the chemical polymer material is 20,000-100,000 Daltons, and the molecular weight of the natural biological polymer material is 300,000-500,000 Daltons.

[0020] Furthermore, the acrylic copolymer is an acrylate-methacrylate copolymer, and its parameters are:

[0021] Molecular weight: 50,000-100,000 Daltons;

[0022] Acid value: 30-60mg KOH / g;

[0023] Viscosity: 1000-5000mPa·s.

[0024] Furthermore, the parameters of the hydroxypropyl methylcellulose are:

[0025] Viscosity: 10,000-100,000 mPa·s;

[0026] Methoxy content: 20-30%;

[0027] Hydroxypropoxy content: 5-12%;

[0028] Degree of substitution: 1.2-1.6;

[0029] Gel temperature: 60℃-75℃.

[0030] The present invention also discloses a method for preparing the above-mentioned atomized biodegradable dust suppressant, comprising the following steps:

[0031] Step S1: Dissolving the substrate:

[0032] Add the substrate to a portion of water, which accounts for 50-60% of the total amount of water, and dissolve it at a temperature of 15°C to 25°C to obtain a uniform solution;

[0033] Step S2, adding thickener:

[0034] Adding a thickener to the uniform solution in step S1 and dissolving it to obtain solution A;

[0035] Step S3, adding film-forming aid:

[0036] adding a film-forming aid to solution A in step S2 to form a stable dispersed phase;

[0037] Step S4, adding surfactant:

[0038] Adding a surfactant to the dispersed phase in step S3 and dissolving it to obtain solution B;

[0039] Step S5: adding preservatives:

[0040] Adding a preservative to the solution B in step S4 and uniformly dispersing the preservative to obtain a solution C;

[0041] Step S6, adding ethanol:

[0042] In step S5, ethanol is added to solution C, and the remaining water is added and mixed evenly to obtain a dust suppressant. Since a portion of the water has been used in step S1, the remaining water is mixed with ethanol to form a dilution solution.

[0043] A dilute solution is prepared by adding ethanol in small amounts to the remaining water multiple times. This mixed dilute solution can not only dilute solution C, but also further reduce the surface tension of the solution, thereby improving the atomization effect of the final solution.

[0044] The beneficial effects of the present invention are: 1. By mixing chemical polymer materials and natural biopolymer materials, the strength and viscosity of the chemical polymer materials are retained, and at the same time, the environmentally friendly degradation performance of the natural biopolymer materials is also brought into play. Biopolymer materials are more easily degraded by microorganisms in the natural environment. By mixing with chemical polymers, the biodegradability of the entire system under specific conditions can be improved, meeting environmental protection requirements. 2. Chemical polymer materials are compounded with natural biopolymer materials to improve the rheological properties of the solution, thereby improving the atomization effect. 3. The dust suppressant obtained after compounding can be dissolved at room temperature while avoiding nozzle clogging. 4. Using a mixture of water and ethanol as a solvent can reduce the surface tension of the solution, which helps to improve the wettability and atomization effect of the liquid; the mixed solvent can make the dust suppressant more easily dispersed into fine droplets during the spraying process, improving the spray uniformity and coverage effect. 5. Ethanol can enhance the solubility of polymer materials, reduce heating requirements, and improve on-site use efficiency. DETAILED DESCRIPTION

[0045] The present invention is described in detail below through specific embodiments.

[0046] The invention discloses an atomizable biodegradable dust suppressant, comprising an active ingredient and an adjuvant, wherein the active ingredient is a base material, and the base material is composed of a chemical polymer material and a natural biopolymer material, wherein the chemical polymer material is polyvinyl alcohol, polyacrylate or polyethylene glycol; the natural biopolymer material is chitosan or xanthan gum; the mass ratio of the chemical polymer material to the natural biopolymer material is 6.5-7.5:3

[0047] The mass percentage of the above active ingredients is 5-20%, the balance is adjuvants, and the sum of the mass percentages of the active ingredients and adjuvants is 100%.

[0048] Chemical polymers possess excellent film-forming and adhesive properties, primarily due to their long molecular chains, which allow them to form a stable, dense film upon drying from a solution. The resulting film is uniform, stable, and strong. This film-forming property also helps form a durable protective layer on the surface, allowing the dust suppressant to adhere to dust particles or surfaces for a longer period of time. The film is smoother, denser, and more resilient, making it less susceptible to cracking or flaking due to environmental factors such as humidity and temperature. Biopolymers, however, have relatively short molecular chains and may exhibit some uneven internal structures upon drying. However, their film-forming properties still offer certain advantages, such as breathability and biodegradability, which offer unique advantages in environmentally friendly applications. They are also more water-soluble and biodegradable, while also producing a more breathable film.

[0049] Single chemical polymer materials can easily lead to high viscosity and nozzle clogging, thus affecting the atomization effect. In the present invention, chemical polymer materials are compounded with natural biological polymer materials to utilize the different properties of the two types of materials to improve the rheological properties of the solution, thereby enhancing the atomization effect.

[0050] Chemical polymer materials have better film-forming properties, and the film layer is smoother, denser, and more elastic. It is not easy to break or peel off due to environmental factors such as humidity and temperature. Biopolymer materials have better water solubility and degradability. At the same time, the film formed is more breathable. The dust suppressant obtained after compounding can be dissolved at room temperature and avoid nozzle clogging.

[0051] When biopolymers are mixed with chemical polymers, they introduce more micropores and voids into the resulting film. These microporous structures allow moisture, oxygen, microorganisms, and other substances to more easily penetrate the film, thereby accelerating the degradation of the chemical polymer. Furthermore, compared to chemical polymers, biopolymers are more hydrophilic, allowing them to fully absorb moisture within the film, promoting the hydrolysis of the chemical polymers and thus accelerating their degradation. Biopolymers themselves are relatively susceptible to microbial degradation. When combined with chemical polymers, the degradation products of the biopolymers, such as small molecule sugars and amines, can provide a nutrient source for microorganisms, further promoting the biodegradation of the chemical polymers. Furthermore, because biopolymers are more easily attached to and utilized by microorganisms, when mixed with chemical polymers, a biofilm forms on or within the film. This biofilm can further break down the structural chains of the chemical polymers, thereby accelerating degradation.

[0052] The chemical polymers mentioned above naturally produce uniform, stable films with high mechanical strength. The addition of biopolymers creates a synergistic effect with the chemical polymers, further enhancing the film's mechanical properties. This is primarily due to two key factors: First, molecular crosslinking: Biopolymers, such as chitosan and xanthan gum, have long molecular chains and complex molecular structures. When mixed with chemical polymers, they can form physical or chemical crosslinks, enhancing the film's structural strength and toughness. This crosslinking increases the film's tensile strength and flexibility, making it less susceptible to breakage under external forces and thus improving its mechanical properties. Second, flexibility and elasticity: Biopolymers possess excellent flexibility and elasticity. Adding them to the film imparts increased flexural strength, making it more resilient to mechanical shock and less susceptible to breakage. This flexibility is particularly useful when the film must withstand various environmental mechanical stresses, such as wind and vibration, and significantly contributes to the dust suppressant's weatherability.

[0053] In this invention, the combination of chemical polymers and natural biopolymers not only retains the strength and viscosity of synthetic polymers, but also improves overall degradation performance, meeting environmental requirements. Natural biopolymers are not only environmentally friendly but also have good biodegradability.

[0054] The supplement contains the following ingredients:

[0055] Thickener: 0.5-2%;

[0056] Solvent: 72.2-93.3%;

[0057] Film-forming aid: 1-5%;

[0058] Surfactant: 0.1-0.5%;

[0059] Preservatives: 0.1-0.3%;

[0060] Wherein, the thickener is hydroxypropyl methylcellulose;

[0061] The solvent is a mixture of water and ethanol, wherein the mass content of water is 90-95% and the mass content of ethanol is 5-10%;

[0062] The film-forming aid is an acrylic acid copolymer;

[0063] The surfactant is sulfosuccinate; preferably octyl glucoside;

[0064] The preservatives are phenoxyethanol and disodium edetate, and the mass ratio of phenoxyethanol to disodium edetate is 2:1.

[0065] The molecular weight of the chemical polymer material is 20,000-100,000 Daltons, and the molecular weight of the natural biopolymer material is 300,000-500,000 Daltons. Both molecular weights are relatively small, and dust suppressants with small molecular weights are prepared.

[0066] The molecular weight of the above-mentioned chemical polymer material is preferably 20,000-100,000 Daltons; the chemical polymer material under this molecular weight can balance solubility, film-forming property and atomization performance, ensuring that the chemical polymer material provides sufficient film-forming ability without affecting the fluidity of the solution and the spray effect, and can dissolve quickly and be easy to use.

[0067] The molecular weight of the natural biopolymer material is preferably 300,000-500,000 Daltons; the natural biopolymer material under this molecular weight enhances the thickening effect, adhesion performance and mechanical strength of film formation, ensuring that the natural biomaterial can provide strong adhesion and film-forming functions for the dust suppressant while maintaining good biodegradability and meeting environmental protection requirements.

[0068] A mixture of water and ethanol was chosen as the solvent because using water alone has the following disadvantages: 1. Poor wettability and atomization of the prepared inhibitor: Water has a higher surface tension than ethanol, resulting in larger droplets during spraying, which affects atomization. This is particularly true when using polymers. Using water alone results in poor dispersion, making it difficult to evenly cover the target surface after spraying. 2. Limited solubility: Polymers, especially high molecular weight materials, dissolve slowly in water, requiring more time for stirring or heating, which affects formulation efficiency, increases process costs, and increases on-site efficiency.

[0069] When using a mixture of water and ethanol, ethanol, as an organic solvent, can reduce the surface tension of the solution, which helps improve wettability and atomization. This mixed solvent allows the dust suppressant to be more easily dispersed into fine droplets during spraying, improving spray uniformity and coverage. Ethanol can enhance the solubility of polymers. By incorporating ethanol, the dissolution rate of polymers in the formulation can be accelerated, reducing heating requirements and improving on-site efficiency. Ethanol's volatility can accelerate the drying of the solution, potentially offering advantages in applications requiring rapid film formation or in humid environments.

[0070] The above-mentioned film-forming aid acrylic copolymer is an acrylate-methacrylate copolymer, and its parameters are:

[0071] Molecular weight: 50,000-100,000 Daltons;

[0072] Acid value: 30-60mg KOH / g;

[0073] Viscosity: 1000-5000mPa·s.

[0074] The main function of the above-mentioned film-forming agents in dust suppressant formulations is to form a uniform film after spraying, firmly fixing dust particles to the ground or other surfaces, preventing them from being re-entrained by wind or other disturbances. The specific functions of film-forming agents in dust suppressants are as follows:

[0075] Capture and fix dust: Film-forming agents form a thin film on the dust suppression surface, which can effectively wrap dust particles, bind them to the surface, and reduce dust resuspension.

[0076] Improve durability: The film formed by the film-forming agent can maintain a stable state for a certain period of time, resist the erosion of external environments such as wind and rain, and prolong the duration of the dust suppression effect.

[0077] Improve adhesion: Film-forming agents can increase the adhesion between dust suppressants and target surfaces, allowing the dust suppressants to evenly cover and firmly adhere to the ground or building surface.

[0078] Waterproof and moisture-proof: Many film-forming agents have certain waterproof properties, which can maintain their dust suppression effect in environments with high humidity and prevent them from becoming ineffective due to rain erosion or humid environments.

[0079] The above-mentioned film-forming agent uses an acrylic copolymer for the following reasons: 1. Excellent film-forming properties: After spraying, acrylic copolymer forms a uniform, dense, and transparent film. Acrylic esters inherently possess excellent film-forming properties, forming a strong film on surfaces, enhancing the durability and stability of the dust suppressant. They maintain their film-forming properties even in low temperatures and high humidity, making them ideal for use in humid environments such as drill-and-blast tunneling. 2. Excellent flexibility and durability: Acrylic copolymer exhibits excellent flexibility and can withstand surface stress without cracking after forming. This makes them suitable for use in environments subject to mechanical disturbances, such as vehicle traffic and equipment operation. Furthermore, this polymer film is resistant to wind and rain, maintaining its dust suppression effectiveness in outdoor environments. 3. Strong weather resistance: Acrylic copolymer exhibits excellent UV and aging resistance, resisting degradation even in strong sunlight. Its film-forming properties are long-lasting, making it suitable for use in environments exposed to the elements, such as coal mines and construction sites. The film-forming layer of this copolymer withstands harsh weather conditions, such as wind and rain, and its film quality is not affected by climate change. 4. Adjustable Physical Properties: Acrylic copolymers can adjust their physical properties, such as hardness and adhesion, by varying the monomer combination. In particular, acrylate-methacrylate copolymers possess both appropriate flexibility and the ability to form relatively hard films, making them suitable for dust suppression in a variety of environments. 5. Environmentally Friendly and Non-Toxic: Acrylic copolymers are non-toxic and biocompatible, resulting in no harmful effects on the surrounding environment or human health during use, meeting modern environmental protection requirements. Their degradation products are relatively safe and do not cause environmental pollution. As a relatively environmentally friendly synthetic polymer, acrylic copolymers have less environmental impact during degradation than some traditional film-forming materials. 6. Easy Processing and Blending: Acrylic copolymers disperse easily in aqueous solutions, eliminating the need for complex dissolution conditions and providing excellent compatibility with aqueous dust suppressant systems. This makes them easy to handle during production and enables excellent dispersion and film formation at room temperature, improving on-site application efficiency and facilitating large-scale industrial production. They also exhibit good compatibility with other ingredients in dust suppressant formulations, such as thickeners, surfactants, and preservatives, ensuring overall performance.

[0080] When dissolved in water, the thickener, hydroxypropyl methylcellulose, increases the solution's flow resistance through intermolecular forces, achieving a thickening effect. Its thickening ability effectively increases the viscosity of the dust suppressant, allowing for a uniform solution distribution during spraying. It also helps the solution quickly form a film after spraying and stably adhere to dust particles, preventing secondary dust dispersion.

[0081] The thickener, hydroxypropyl methylcellulose, exhibits shear-thinning properties, meaning that under shear forces, such as during spraying, the solution's viscosity decreases, reducing the risk of nozzle clogging. This property ensures that the solution flows smoothly through the nozzle during spraying, forming fine droplets and improving atomization. It also restores its original viscosity after spraying, enabling rapid film formation.

[0082] The thickener, hydroxypropyl methylcellulose, has film-forming properties. After spraying, it forms a uniform protective film on the surface of dust particles. This film effectively captures and secures dust particles, preventing them from being dispersed with air. HPMC's excellent film-forming properties ensure the film possesses sufficient mechanical strength and weather resistance, making it suitable for use in drill-and-blast tunneling environments.

[0083] The thickener, hydroxypropyl methylcellulose, has excellent water retention, allowing it to maintain a certain humidity in dry environments, extending the duration of the dust suppressant's action. This water retention helps the dust suppressant remain moist for longer after application, further securing the dust and preventing wind or other environmental factors from affecting the dust suppression effect.

[0084] In order to ensure the best effect of hydroxypropyl methylcellulose in the formulation, its parameters are selected as follows:

[0085] Viscosity: 10,000-100,000 mPa·s;

[0086] Methoxy content: 20-30%;

[0087] Hydroxypropoxy content: 5-12%;

[0088] Degree of substitution: 1.2-1.6;

[0089] Gel temperature: 60℃-75℃.

[0090] The viscosity range of HPMC directly impacts its thickening effect and rheological properties. This formulation selects a viscosity range of 10,000-100,000 mPa·s to ensure that the dust suppressant solution, at a concentration of 0.5%-2%, has an appropriate viscosity. This allows for good fluidity and atomization during spraying, while also allowing for rapid film formation after spraying. Lower viscosities can result in insufficient film formation, while higher viscosities can lead to nozzle clogging.

[0091] The methoxy content affects the solubility and gelation temperature of HPMC. A higher methoxy content lowers the gelation temperature, allowing the solution to gel at a lower temperature, which helps it form a film quickly after spraying. A methoxy content of 20-30% ensures that HPMC is fully soluble at room temperature and quickly solidifies into a film after spraying, making it suitable for use in drill-and-blast tunneling environments in coal mines.

[0092] The hydroxypropoxy content affects the flexibility and transparency of HPMC. A higher hydroxypropoxy content increases the flexibility and weather resistance of the formed film, making it less susceptible to cracking under external stress. A hydroxypropoxy content of 5-12% ensures that the formed film has sufficient flexibility to be suitable for long-term use in drill-and-blast tunneling environments.

[0093] The degree of substitution (DS) determines the number of substituted hydroxyl groups in the HPMC molecule, which affects its water solubility and thickening performance. A higher DS improves HPMC's water solubility, allowing it to dissolve quickly and distribute evenly in the solution. A DS of 1.2-1.6 ensures that HPMC achieves both thickening and film-forming properties at lower concentrations.

[0094] HPMC's gelation temperature determines its phase transition behavior upon heating. Selecting a gelation temperature between 60°C and 75°C ensures that HPMC resists gelation at room temperature while rapidly forming a film at higher temperatures, making it suitable for use in drill-and-blast tunneling environments. This temperature range also ensures that HPMC's dust suppression effectiveness is not affected by ambient temperature fluctuations during use.

[0095] The above-mentioned surfactants reduce the surface tension of the liquid, making it easier for the liquid to disperse into fine droplets, and can better cover the dust particles, thereby improving the dust suppression effect.

[0096] Sulfosuccinate surfactants are a type of anionic surfactant with good biodegradability, low toxicity, and excellent wetting and dispersing properties. The details are as follows:

[0097] 1. Good wettability and dispersibility:

[0098] Wetting properties: Sulfosuccinate surfactants can significantly reduce the surface tension of water by approximately 25-30 mN / m, thereby improving the wetting properties of liquids. This allows the dust suppressant to quickly wet the particle surface when sprayed onto the dust surface, forming a uniform dust suppression film.

[0099] Dispersibility: This type of surfactant has good dispersibility, which can help the various components of the dust suppressant to be evenly distributed in the solution, avoiding precipitation or stratification during storage or use.

[0100] 2. Good atomization performance:

[0101] Sulfosuccinate surfactants, due to their strong surface activity, can effectively reduce surface tension, helping liquids to be atomized into fine droplets. This is crucial in atomization dust suppression applications, as the smaller the droplets, the larger the area covered, and the better the dust suppression effect.

[0102] Experiments show that dust suppressants with the addition of this type of surfactant can produce smaller and more uniform droplets during the spraying process, further improving the coverage and dust suppression effect.

[0103] 3. Biodegradability and environmental protection:

[0104] Environmental Performance: Sulfosuccinate surfactants are highly biodegradable and rapidly degrade into harmless substances in the environment, meeting environmental requirements. This is particularly important for large-scale dust suppressant applications, such as those in drill-and-blast tunneling. Using environmentally friendly surfactants can significantly reduce long-term impacts on the environment and worker health.

[0105] Low toxicity: Compared with other types of anionic surfactants, sulfosuccinate surfactants have lower toxicity and are less harmful to aquatic organisms. They are suitable for use in dust suppressant formulations that require high environmental standards.

[0106] 4. Hard water resistance:

[0107] Sulfosuccinate surfactants have excellent resistance to hard water and are not easily affected by calcium and magnesium ions in water, maintaining their surface activity. This is particularly beneficial when formulating dust suppressants using hard water, ensuring that the performance of the dust suppressant is not significantly affected even in hard water conditions.

[0108] In drill-and-blast tunneling environments, industrial water or natural water sources are often used, which often contain high levels of hard water ions. The use of sulfosuccinate surfactants ensures that dust suppressants work stably under various water quality conditions.

[0109] 5. Thermal stability and weather resistance:

[0110] Sulfosuccinate surfactants have good thermal stability and can maintain their surface activity at higher temperatures. This is particularly important when used in high-temperature environments such as drill-and-blast tunneling.

[0111] Under high temperature or exposure to strong ultraviolet rays, this type of surfactant can still maintain its good activity and will not degrade or fail quickly, ensuring the long-term dust suppression effect of the dust suppressant.

[0112] The role of these preservatives in dust suppressant formulations is to inhibit or slow the growth of microorganisms, thereby extending the shelf life of the dust suppressant and ensuring its stable performance during storage and use. Because dust suppressant solutions often contain water, organic matter, and other components that are easily exploited by microorganisms, microorganisms can easily grow in them, leading to product deterioration, reduced effectiveness, or a change in odor.

[0113] Phenoxyethanol: Broad-spectrum antimicrobial activity; relatively low toxicity and safety; Good environmental performance: Phenoxyethanol is highly biodegradable and breaks down relatively quickly in the natural environment, meeting environmental requirements; Mild antiseptic effect: Compared to more potent preservatives, phenoxyethanol has a milder antiseptic effect and is less likely to react with other ingredients, thus avoiding chemical instability in the solution. Furthermore, its relatively mild odor makes it suitable for dust suppressants requiring long-term storage and large-area spraying.

[0114] Disodium Ethylenediaminetetraacetic Acid: Strong Chelating Ability: EDTA-2Na is a highly effective chelating agent that binds to metal ions (such as calcium, magnesium, and iron) in solution, inhibiting their utilization by microorganisms and indirectly preventing their growth. Metal ions are essential for the metabolism of many microorganisms. EDTA inhibits microbial growth by chelating metal ions, thus providing an antiseptic effect. Good Chemical Stability: EDTA-2Na is highly chemically stable and maintains its effectiveness under varying pH conditions, making it suitable for various water-soluble dust suppressant formulations. Hard Water Compatibility: EDTA-2Na chelates calcium and magnesium ions in hard water, preventing their deposition and scaling. This is particularly important in industrial water sources, especially when formulating dust suppressants using hard water. EDTA-2Na helps maintain solution clarity and stability, preventing precipitation and stratification caused by hard water. Auxiliary Antimicrobial Effect: While not a direct antimicrobial agent itself, EDTA-2Na can enhance the effectiveness of other preservatives by chelating metal ions. Therefore, EDTA-2Na is often used together with other preservatives to enhance the overall preservative performance.

[0115] The effects of phenoxyethanol and EDTA-2Na complement each other: phenoxyethanol mainly inhibits the growth of bacteria, fungi and yeast through direct broad-spectrum antibacterial effects, playing a primary antiseptic role; EDTA-2Na indirectly inhibits the utilization of metal ions by microorganisms by chelating metal ions in the solution, thereby enhancing the antiseptic effect and having an auxiliary antibacterial function.

[0116] The preparation method of the above-mentioned atomized biodegradable dust suppressant comprises the following steps:

[0117] Step S1: Dissolving the substrate:

[0118] The substrate is added into a portion of water, which accounts for 50-60% of the total amount of water, and stirred and dissolved at a temperature of 15°C to 25°C to obtain a uniform solution; 15°C to 25°C is room temperature, which helps to avoid unnecessary chemical reactions or decomposition due to excessively high temperature during the dissolution of the substrate, while reducing energy consumption.

[0119] Stirring rate: Maintain at 300-500 rpm for 30 minutes to 1 hour, until the substrate is completely dissolved and a uniform solution is formed. This moderate stirring rate provides sufficient shear force to accelerate substrate dissolution while preventing foaming and uneven composition. Stirring for 30 minutes to 1 hour ensures complete dissolution of the substrate, resulting in a uniform solution that facilitates subsequent thickening and film-forming agent addition. Shorter stirring times will result in incomplete dissolution, while longer stirring times are unnecessary and increase energy consumption.

[0120] Step S2, adding thickener:

[0121] In the homogeneous solution obtained in step S1, a thickener is gradually added, preferably hydroxypropyl methylcellulose HPMC, and dissolved to obtain solution A;

[0122] Stirring rate: Maintain at 300-400 rpm for 30 minutes to ensure that the thickener is completely dissolved and Solution A becomes viscous and uniform.

[0123] If it does not dissolve well, you can increase the temperature to 30-40°C to speed up the dissolution of the thickener. A slightly higher temperature helps the molecular chain of the thickener to expand, thereby speeding up its dissolution.

[0124] Step S3, adding film-forming aid:

[0125] Add the film-forming aid to Solution A in step S2 while stirring. Maintain a gentle stirring rate of 200-300 rpm to achieve complete dissolution. Stir for 15-30 minutes until the film-forming aid is evenly dispersed in Solution A and forms a stable dispersed phase.

[0126] This speed is suitable for uniform dispersion of the film-forming aid. The dissolution of the film-forming aid in the solution requires gentle stirring to avoid flocculation or uneven dispersion of the film-forming aid due to excessive shearing.

[0127] The time is set to ensure that the film-forming aid is completely dissolved and forms a stable dispersed phase, thus providing a good foundation for the subsequent addition of surfactants. Generally, the substrate can be dissolved within this time.

[0128] Step S4, adding surfactant:

[0129] Add a surfactant to the dispersed phase in step S3. Add the surfactant slowly to prevent excessive foaming. Stir at a relatively low stirring rate of 150-200 rpm for 15 minutes until the surfactant is completely dissolved and no bubbles are visible on the surface of the solution, yielding Solution B.

[0130] Since surfactants tend to foam, slow addition can prevent excessive foaming. Low-speed stirring can ensure uniform distribution of surfactants.

[0131] Step S5: adding preservatives:

[0132] Add a preservative to the solution B in step S4; maintain a stirring rate of 200-300 rpm and stir for 10-20 minutes until the preservative is evenly dispersed to obtain a solution C.

[0133] Step S6, adding ethanol and diluting:

[0134] According to the formulation requirements, the remaining water and ethanol mixture is added to the solution C in step S5 to dilute the solution to the target concentration.

[0135] Operation requirements: Ethanol should be added in batches to avoid excessive foaming or volatilization of the solution. The stirring rate should be maintained at 150-300 rpm for 20 minutes to ensure that the ethanol is evenly mixed in to obtain solution D, which is the dust suppressant.

[0136] Batch addition means adding the ethanol in small portions, rather than all at once. This is done to avoid rapid evaporation of the ethanol or excessive foaming of the solution, and to ensure that the ethanol is evenly mixed into the solution.

[0137] During operation, you can slowly pour a portion of ethanol into the solution first, stir until fully mixed, and then add the next batch. The amount added to each batch can be adjusted according to the stirring effect and the state of the solution to ensure uniform mixing.

[0138] Adding ethanol in batches can avoid rapid evaporation of ethanol or excessive foaming of the solution, and it is easier to control the uniformity and viscosity of the solution.

[0139] After obtaining the dust suppressant, in order to facilitate storage and use, it also includes the following:

[0140] Step S7, adjusting the pH of solution D:

[0141] Use a weak acid or base, such as citric acid or sodium bicarbonate, to adjust the pH of Solution D to 6.5-7.5 to ensure product stability and performance. The pH range of 6.5-7.5 is designed to ensure solution stability and optimize performance. Weak acids or bases, such as citric acid or sodium bicarbonate, can safely adjust the pH without affecting the main components of the solution.

[0142] Step S8, final stirring and filtration:

[0143] After all ingredients are added, stir at a low speed of 100-200 rpm for 20-30 minutes to ensure complete and uniform mixing to obtain a mixed solution. The final stage of stirring is to ensure the final uniform mixing of all ingredients while avoiding excessive shearing.

[0144] The mixed solution is filtered through a 200-mesh filter to remove undissolved impurities and ensure the uniformity and purity of the mixed solution. Filtration can remove undissolved particles or impurities in the solution to ensure the purity and uniformity of the product.

[0145] Step S9: Packaging and storage:

[0146] Place the filtered mixture into a clean storage container and store it tightly closed at 5°C to 25°C, away from light and extreme temperatures. Sealing the container at 5°C to 25°C will help extend the shelf life of the solution and prevent the components from breaking down or becoming ineffective due to light or extreme temperatures.

[0147] Storage conditions: This solution has good stability and can be stored at room temperature for 6 months to 1 year.

[0148] In order to further verify the atomized biodegradable dust suppressant and preparation method of the present invention, specific embodiments are described in detail, and each embodiment is shown in Table 1:

[0149] Table 1 Examples

[0150]

[0151]

[0152] The above cases 1-4 and 9-24 are embodiments, and 5-8 are comparative examples.

[0153] In the table, the chemical polymer material used in cases 1-10 and 12-24 is PEG, and the chemical polymer material used in case 11 is PAA.

[0154] In the table, the biopolymer material used in cases 1-11, 13-24 is chitosan, and the biopolymer material used in case 12 is xanthan gum.

[0155] In the case in the table, the thickener is hydroxypropyl methylcellulose, the film-forming aid is acrylate-methacrylate copolymer, and the surfactant is octyl glucoside.

[0156] The inhibitors in each case in Table 1 were verified and evaluated, and atomization effect; film forming property; durability; dust suppression efficiency; and biodegradability were selected as evaluation indicators for the dust suppression effect of dust suppressants.

[0157] Atomization effect: average droplet diameter;

[0158] Film forming property: film forming time;

[0159] Durability: The dust suppressant film can withstand continuous wind and rain for a long time;

[0160] Dust suppression efficiency: dust suppression ratio;

[0161] Biodegradability: How long does it take for the dust suppressant to completely degrade?

[0162] The evaluation results are shown in Table 2:

[0163] Table 2 Evaluation results of each embodiment

[0164]

[0165]

[0166] Case 1: The average droplet diameter is 80μm, and the droplets are evenly distributed. A transparent and uniform film is formed within 20 minutes after spraying. The film remains intact under continuous wind and rain conditions, and there is no obvious damage during the 48-hour test. The dust suppression efficiency is 95%, effectively suppressing secondary dust.

[0167] Case 2: In this case, the content of film-forming aid was increased, resulting in more uniform droplets. However, some larger droplets affected the coverage, resulting in a thicker film with significantly improved film strength and sealing effect, effectively suppressing the resuspension of dust.

[0168] Case 3: In this case, the ethanol ratio was reduced, and the average droplet diameter was 70μm. The droplets were small and evenly distributed, with a wider coverage area. The film formation time was extended to 30 minutes, and the film was relatively thin, but the coverage was uniform. The film was partially damaged after being exposed to wind and rain for 24 hours, and the overall weather resistance was weak. The dust suppression efficiency was 93%, and the atomization effect was improved, but the film was thin, and the dust suppression effect was slightly reduced under adverse conditions.

[0169] Case 4: In this case, no thickener was added, the average droplet diameter was 60μm, the droplets were very small and uniform, and the atomization effect was optimal; since no thickener was added, the film was relatively thin, the formation time was 40 minutes, and the film layer was uneven; the film was damaged after being exposed to external conditions for 12 hours, and the weather resistance was poor; the dust suppression efficiency was 85%, and although the atomization effect was good, the film forming property and durability were insufficient, resulting in unsatisfactory dust suppression effect.

[0170] Case 5: In this case, no film-forming agent was added, the average droplet diameter was 70 μm, and the droplet distribution was relatively uniform. However, due to the lack of film-forming agent, the droplet adhesion after spraying was slightly poor. The film formed after spraying was thin and uneven, and it took 30 minutes for the film to completely cover the dust particles. The film had a short resistance time to wind and rain, and the film layer showed obvious damage after 12 hours. The dust suppression efficiency was 88%, which was lower than that of the basic formula. The dust was easily re-blown under wind conditions, forming secondary dust. The formula completely degraded within 60 days without obvious residue, and the degradation rate was relatively fast.

[0171] Case 6: In this case, no surfactant was added, and the average droplet diameter was 110 μm. The droplets were large and unevenly distributed, making it difficult for the droplets formed during the spraying process to effectively cover the dust. Due to the large droplets, the film formed was thicker, but the coverage was uneven, and the film was completely formed within 25 minutes. The film performed well within 24 hours, but due to the initial uneven coverage, some areas were damaged by rain. The dust suppression efficiency was 80%, and the atomization effect was poor, resulting in uneven dust suppression coverage and a significant decrease in the dust suppression effect. The film gradually degraded within 90 days, and the degradation rate was relatively slow.

[0172] Case 7: In this case, the substrate only uses chemical polymer materials, the average droplet diameter is 90μm, the droplets are relatively uniform, but the covering ability is weak; due to the use of only chemical polymers, the film-forming speed is slow and the film layer is thin, and the film is completely formed after 40 minutes; the film partially peels off after being exposed to wind and rain for 18 hours; the dust suppression efficiency is 85%, and although the film is formed, the overall adhesion performance is poor, and the dust is easily raised again under strong winds; the chemical polymer material degrades slowly, and some of the film still remains after 120 days.

[0173] Case 8: The substrate in this case only uses natural biopolymer materials, the average droplet diameter is 65μm, the droplets are evenly distributed and cover a wide area; the film is formed within 25 minutes, the film layer is uniform and transparent, and has good adhesion; the film lasts for 24 hours under wind and rain conditions without obvious damage; the dust suppression efficiency is 85%, the dust suppression effect is general, and it can fix dust for a certain period of time; chitosan is completely degraded within 60 days, and will not pollute the environment after degradation.

[0174] Case 9: The total content of the substrate in this case is 5%, which reduces the amount of substrate used. Its atomization effect and biodegradability are improved, but its film-forming property, durability and dust suppression efficiency show a downward trend.

[0175] Case 10: The total content of the substrate in this case is 20%, and the amount of substrate used is increased.

[0176] Case 11: The chemical polymer material used in this case is PAA, and its atomization effect, dust suppression efficiency and biodegradability are slightly lower than those in Case 1.

[0177] Case 12: The biopolymer material used in this case is xanthan gum.

[0178] Case 13: In this case, the ratio of chemical polymer materials to biopolymer materials is 6.5:1.

[0179] Case 14: In this case, the ratio of chemical polymer materials to biopolymer materials is 7.5:1.

[0180] Case 15: In this case, the mass content of thickener accounts for 0.5% of the total mass content. The results show that the atomization effect is slightly more significant than that of Case 1, and the overall result is within the expected range.

[0181] Case 16: In this case, the mass content of thickener accounts for 2% of the total mass content. The results show that the atomization effect is slightly worse than that of Case 1.

[0182] Case 17: In this case, the mass content of the film-forming aid accounts for 1% of the total mass content. As a result, it can be seen that the film formation is slow.

[0183] Case 18: In this case, the mass content of the film-forming aid accounts for 1% of the total mass content. The results show that the film is formed faster.

[0184] Case 19: In this case, the surfactant content accounts for 0.1% of the total mass content.

[0185] Case 20: In this case, the surfactant content accounts for 0.5% of the total mass content.

[0186] Case 21: In this case, the mass content of preservatives accounts for 0.1% of the total mass content.

[0187] Case 22: In this case, the solvent content accounts for 72.2% of the total mass content. Compared with Case 1, the usage ratio of the remaining components is increased. It can be seen that as the usage ratio of each functional agent increases, the dust suppression efficiency does not increase significantly, and the atomization effect, film-forming property and biodegradability decrease slightly.

[0188] Case 23: In this case, the solvent content accounts for 93.3% of the total mass content. As the proportion of each functional agent used decreases, the atomization effect is improved, but the film-forming property and dust reduction efficiency are slightly inferior to those in Case 1.

[0189] Case 24: The ethanol content in the solvent in this case accounts for 10% of the total mass content. Its usage ratio has increased compared with Case 1, and its atomization effect has improved compared with Case 1, but its film-forming property, durability, dust suppression efficiency and biodegradability are all lower than those in Case 1.

[0190] Comprehensive comparison shows that Case 1 has the best effect.

[0191] The use of dust suppressants is as follows:

[0192] This dust suppressant can be applied directly to tunnel excavations and other dust-generating areas using standard spray equipment. The dust suppressant solution is atomized and sprayed onto the desired area. After application, the dust suppressant quickly forms a thin film on the desired surface, such as the tunnel wall, effectively capturing and immobilizing dust particles and reducing secondary dust entrainment.

[0193] The dust suppressant can form a stable film on the surface within 24 hours and remain effective in harsh environments such as wind and rain, and has good weather resistance.

[0194] In addition, due to the biodegradability of its components, the dust suppressant will not cause persistent pollution to the environment after use, can be naturally degraded, and will not affect people's health.

Claims

1. An atomizable biodegradable dust suppressant, characterized in that: It comprises an effective component and an auxiliary agent, wherein the effective component is a substrate, and the substrate is composed of a chemical polymer material and a natural biological polymer material, wherein the chemical polymer material is polyvinyl alcohol, polyacrylate or polyethylene glycol; and the natural biological polymer material is chitosan or xanthan gum; The mass percentage of the active ingredient is 5-20%, the remainder is auxiliary agent, and the sum of the mass percentages of the active ingredient and the auxiliary agent is 100%.

2. The atomizable biodegradable dust suppressant according to claim 1, characterized in that: The mass ratio of the chemical polymer material to the natural biological polymer material is 6.5-7.5:

3.

3. The atomizable biodegradable dust suppressant according to claim 2, characterized in that: The auxiliary agent comprises the following ingredients: Thickener: 0.5-2%; Solvent: 72.2-93.3%; Film-forming aid: 1-5%; Surfactant: 0.1-0.5%; Preservatives: 0.1-0.3%; Wherein, the solvent is a mixture of water and ethanol, in which the mass content of water is 90-95%, and the mass content of ethanol is 5-10%.

4. The atomizable biodegradable dust suppressant according to claim 3, characterized in that: The thickener is hydroxypropyl methylcellulose; The film-forming aid is an acrylic acid copolymer; The surfactant is sulfosuccinate; The preservatives are phenoxyethanol and disodium ethylenediaminetetraacetate, and the mass ratio of phenoxyethanol to disodium ethylenediaminetetraacetate is 2:

1.

5. The atomizable biodegradable dust suppressant according to claim 4, characterized in that: The molecular weight of the chemical polymer material is 20,000-100,000 Daltons, and the molecular weight of the natural biological polymer material is 300,000-500,000 Daltons.

6. The atomizable biodegradable dust suppressant according to claim 5, characterized in that: The acrylic copolymer is an acrylate-methacrylate copolymer, and its parameters are: Molecular weight: 50,000-100,000 Daltons; Acid value: 30-60mg KOH / g; Viscosity: 1000-5000mPa·s.

7. The atomizable biodegradable dust suppressant according to claim 6, characterized in that: The parameters of the hydroxypropyl methylcellulose are: Viscosity: 10,000-100,000 mPa·s; Methoxy content: 20-30%; Hydroxypropoxy content: 5-12%; Degree of substitution: 1.2-1.6; Gel temperature: 60℃-75℃.

8. A method for preparing an atomized biodegradable dust suppressant according to any one of claims 1 to 7, characterized in that: The steps include: Step S1, substrate dissolution: The substrate is added into a portion of water, which accounts for 50-60% of the total amount of water, and dissolved at a temperature of 15°C to 25°C to obtain a uniform solution; Step S2, adding thickener: Adding a thickener to the uniform solution in step S1 and dissolving it to obtain solution A; Step S3, adding film-forming aid: Adding a film-forming aid to the solution A in step S2 to form a stable dispersed phase; Step S4, adding surfactant: Adding a surfactant to the dispersed phase in step S3 and dissolving it to obtain solution B; Step S5, adding preservatives: Adding a preservative to the solution B in step S4 and dispersing the preservative uniformly to obtain a solution C; Step S6, adding ethanol: Add ethanol to the solution C in step S5, and add the remaining water, mix well, and obtain the dust suppressant. Since a part of the water has been used in step S1, the remaining water is mixed with ethanol to form a dilution solution. The diluted solution obtained by adding ethanol to the remaining water in small amounts for multiple times can not only dilute solution C, but also further reduce the surface tension of the solution, thereby improving the atomization effect of the final solution.